Husband’s Role in Caring for Stunted Children: Patriarchal Culture Perspective in Kupang - Joli Riyana Nubatonis; Prima Dewi Kusumawati; Byba Melda Suhita (GLOBAL HEALTH SCIENCE GROUP, 2025)
Patriarchal culture shapes gender roles in childcare, often restricting fathers’ involvement and placing the main caregiving responsibility on mothers. Such conditions may contribute to child health problems, particularly stunting, which remains a significant public health challenge in Indonesia, especially in East Nusa Tenggara. This study aimed to explore husbands’ behaviour in caring for children with stunting from the perspective of patriarchal culture in Tarus Village, Kupang Regency. A qualitative exploratory research with an ethnographic approach was conducted through in-depth semi-structured interviews involving eight participants (four husbands and four wives) who met the inclusion criteria. Data were analysed using Interpretative Phenomenological Analysis (IPA). The analysis generated five major themes: (1) dominance of patriarchal culture, (2) limited involvement of husbands, (3) gender-based affection and stimulation, (4) emotional challenges in managing stunting, and (5) hope and resilience. These findings demonstrate how patriarchal norms restrict the father’s role and reinforce the mother’s primary responsibility in childcare. Patriarchal values significantly influence childcare practices, resulting in minimal paternal involvement in preventing stunting. To address this, gender-sensitive interventions are required, including father-focused training, public awareness campaigns, and family-supportive policies to strengthen paternal roles and reduce stunting prevalence.